SCIENTIFIC AND THEORETICAL FOUNDATIONS OF DYSARTHRIA SPEECH DISORDER - Iminjonova Mokhichehra Alimardon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article analyzes the scientific and theoretical foundations of dysarthria speech disorder, including the damage to the central and peripheral nervous systems that causes its occurrence, and the impairment of motor functions of the speech apparatus. Based on a scientific approach, the clinical manifestations, pathogenesis, and influence of dysarthria on phonetic-phonemic processes are highlighted, as well as the degrees of impairment in respiratory, vocal, and articulatory mechanisms. The article also theoretically substantiates neurological factors associated with dysarthria, psycholinguistic mechanisms, speech therapy diagnostic methods, and correctional-pedagogical technologies. Additionally, modern scientific research and methodological approaches to studying and correcting speech in children with dysarthria are presented.